Diversity and population structure of Criollo Lechero Tropical and Romosinuano cattle breeds in Mexico - Martínez Rocha, Ricardo E; Parra Bracamonte, Gaspar Manuel; Ramírez Valverde, Rodolfo; Núñez Domínguez, Rafael; García Muñiz, José G (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: The assessment of genetic diversity, population structure, as well as within and across breed relationships using DNA markers is essential to develop conservation and genetic improvement programs. Objective: To assess the genetic diversity and population structure of Criollo Lechero Tropical (CLT) and Romosinuano (ROMO) cattle breeds in Mexico and compare them with other Criollo and Spanish breeds. Methods: The study included CLT and ROMO genotypes from the 65k Axiom©BovMDv3 array. Genomic data of Criollo and Spanish breeds were retrieved from a repository. Genetic diversity across breeds was evaluated by pairwise Wright's FST, principal components, and structure analysis. Results: Observed and expected heterozygosity, inbreeding coefficient, and effective population size (Ne) were 0.31, 0.30, -0.018 and 56 in CLT, and 0.32, 0.31, -0.023 and 99 in ROMO, respectively. Wright's FST indicated that both breeds are related to American Criollo and some Spanish cattle. ROMO cattle showed more significant Spanish ancestry than CLT. Conclusions: This study presents novel evidence indicating that, although the Ne of these breeds is small, they are still diverse and can be used as genetic reservoirs in conservation programs.